Diagnosis Discordance and Neonatal Transport: A Single-Center Retrospective Chart Review - Sampaio, Tatiana Z. A. L.; Wilson, Margo; Aubertin, Cheryl; Redpath, Stephanie (American Journal of Perinatology, 2019)
Introduction In Canada, more than 4,000 critically ill newborns per year require transfer. Transports are initially managed based on information conveyed by referral practitioners.Objectives To identify the frequency of diagnostic discordance between the referring facility, transport team, and tertiary care center in our outborn neonatal population and to verify the association between discordance events (DEs), prolonged transport stabilization times, and potential risk factors to further inform and facilitate the development of future outreach education initiatives.Study Design In this retrospective chart review, we identified and categorized DEs for patients transported by our service in a 1-year period. Associations between DE, transport stabilization times, and patient variables were studied using univariate and multivariable approaches.Results From 233 eligible patients, 10.7% of patients had referral to discharge discordance events. No significant association was identified between stabilization time and DE. Birth weight and presence of a neurologic diagnosis were associated with DE.Conclusion Diagnostic discordance was identified in 1 of every 10 neonates transported and found to be associated with patients with higher birth weight and the presence of neurologic diagnoses. Outreach initiatives will be developed and adapted accordingly, with a focus on this population.
Keywords: interfacility transport; newborn; outborn; diagnosis discordance